K-Means Analysis of West Java Coastal Capture Fish Production to Increase Fisheries Productivity - Siti Salwa Azzahra; Fatia Amalia Maresti; Kiki Mustaqim (Universitas Mohammad Husni Thamrin, 2026)
Marine capture fisheries in West Java play a vital role in regional economic development, yet disparities in productivity among coastal areas remain unresolved. This study aims to classify coastal districts and cities in West Java based on key production indicators: fish catch volume, number of vessels, number of marine fishers, average weighted price per kilogram, and the number of fishing households. A K-Means Clustering approach was applied to group these regions into homogeneous clusters, enabling more targeted policy development. The analysis identified three distinct clusters: moderately productive areas with low efficiency, economically efficient areas with high-value catch but limited volume, and a dominant production zone with significantly higher outputs than others. These findings provide a clearer understanding of regional fishery dynamics and offer recommendations for each cluster. Proposed strategies include expanding infrastructure and training for low-performing regions, and focusing on product diversification, post-harvest processing, and sustainable management in high-performing areas. This study demonstrates the usefulness of data-driven methods to support marine fishery development and regional planning.